Intelligent home automated system - R MF Amin; R FA Yasmin; A. N. Azlina; AB Zanariah; Y Faridah (Institute of Advanced Engineering and Science, 2019)
Home automation system is one of the intelligent systems meant to create new opportunities for industry and business, as well as new experiences for users and consumers. This project is about designing, developing and testing a web-based intelligent home automation system called i-Home. The main users will be residents in any residential area i.e. gated community, terrace housing area, condominium and others. Its function is to ease residents in controlling the lights, fans, air conditioning, the house temperature and monitoring their CCTVs through online. For the hardware component Raspberry Pi was used due to its low cost, credit card-sized single-board computer that includes a processor, GPU, RAM and MicroSD as the server. Raspberry Pi primarily uses Linux-kernel-based operating system. It also requires PHP, JavaScript, Python and MySQL. The prototype of the system was built and performed most of the functions of home automation system. Usability and functional testing were carried out and both results showed that all functions worked perfectly.